The quiet eye provides preplanning and online control support for interceptive task performance - Sun, G.; Zhang, L.; Vine, S. J.; Wilson, M. R. (Journal of Sport & Exercise Psychology, 2016)
Longer quiet eye (QE) periods are associated with better performance across a range of targeting and interceptive tasks. However, the direction of this relationship is still unclear. The two studies presented aimed to narrow this knowledge gap by experimentally manipulating QE duration—by delaying its onset or by truncating its offset—in an aiming interceptive task. In Experiment 1, the early trajectory was occluded, causing significantly shorter QE durations and worse subsequent performance. In Experiment 2, both early and/or late trajectory were occluded. Performance was degraded by the occlusion of either early or late information, and the worst performance occurred when both the early and late trajectory were occluded. Taken together, the results suggest that QE is not a by-product of performance but instead plays a causal role in supporting the interception of a moving target through a combination of preprogramming and online control processes.